LINGVOCULTUROLOGY AND PAREMIOLOGICAL ASPECTS OF A LANGUAGE - Valieva M. S. (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the issues of studying linguoculturology, explores and compares the development of linguoculturology both in Russian and in Uzbek linguistics. Also, the question of the appearance of proverbs from a cognitive point of view and the paremiological aspect of the language are considered.